2023
DOI: 10.1051/e3sconf/202340211001
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties magnetically elastic material samples under extreme compression modes

Abstract: The magnetoelastic material samples in compression tests are investigated. The studied materials rheological properties are carried out on an automated testing machine. Compressive moduli changes diagrams depending on deformation values up to limiting extreme values are plotted. Transition ranges from linear to nonlinear, longitudinal compression moduli, depending on the specimen compression degree, were fixed. Repeated tests on specimens showed a decrease in the compression moduli by several times. In reveali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In previous studies [7,8], it was shown that a sample of magnetically active composite demonstrated unique capabilities of the material to self-repair of shape under extreme compression up to 10 kN. Namely, under repeated, more than 500%, elastic stretching of the sample in transverse, horizontal direction and, respectively, under compression in height up to 96%.…”
Section: Findings and Possible Research Directionsmentioning
confidence: 99%
“…In previous studies [7,8], it was shown that a sample of magnetically active composite demonstrated unique capabilities of the material to self-repair of shape under extreme compression up to 10 kN. Namely, under repeated, more than 500%, elastic stretching of the sample in transverse, horizontal direction and, respectively, under compression in height up to 96%.…”
Section: Findings and Possible Research Directionsmentioning
confidence: 99%